On the link between fiscal decentralization and public debt in OECD countries - Baskaran, Thushyanthan (Public choice, 2010)
Excessive borrowing by subnational governments is considered to be one of the perils of fiscal decentralization. On the other hand, fiscal decentralization might ensure the fiscal stability of the public sector by constraining Leviathan governments. Since the impact of decentralized government on fiscal outcomes is therefore ambiguous from a theoretical perspective, we explore this question empirically with a panel of 17 OECD countries over the 1975-2001 period. Our findings suggest that expenditure decentralization significantly reduces public indebtedness, whereas tax decentralization and vertical fiscal imbalances are insignificant.
Published online: 21 November 2009
Gesehen am 07.12.2022